2010
DOI: 10.1016/j.oraloncology.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck cancer in a developing country: A population-based perspective across 8years

Abstract: Summary Head and Neck Cancer (HNC) has been studied in different regions of the world but little is known about its incidence patterns in the Middle East and Egypt. In this study from Egypt’s only population-based registry, we analyzed data from 1999-2006, to estimate incidence, incidence rate ratios (IRRs) and 95% confidence intervals (CIs) categorized by age, district and subsites. Overall urban incidence of HNC was twice or more that of rural incidence for both males (IRR = 2.59; 95% CI = 2.26, 2.97) and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 26 publications
6
60
1
1
Order By: Relevance
“…This risk factor seems to be related to exposure to an intermediate metabolite of ethanol, acetaldehyde, which is a known carcinogen 20 . When analyzing the socio-demographic profile of the patients included in this study, a higher prevalence of cancer diagnoses and deaths was observed amongst males, which was also reported in other studies [23][24][25] . There is evidence that exposure to tobacco is higher in men than in women 26 , and that women notice the symptoms of the disease more easily than men, which may lead them to seek medical assistance earlier 23 , thus resulting in earlier diagnosis and improved survival.…”
Section: Discussionsupporting
confidence: 85%
“…This risk factor seems to be related to exposure to an intermediate metabolite of ethanol, acetaldehyde, which is a known carcinogen 20 . When analyzing the socio-demographic profile of the patients included in this study, a higher prevalence of cancer diagnoses and deaths was observed amongst males, which was also reported in other studies [23][24][25] . There is evidence that exposure to tobacco is higher in men than in women 26 , and that women notice the symptoms of the disease more easily than men, which may lead them to seek medical assistance earlier 23 , thus resulting in earlier diagnosis and improved survival.…”
Section: Discussionsupporting
confidence: 85%
“…Similar findings found in another studies where, mean age of patients was 52.6 years and 59.5 years respectively. 1,14 All the above studies reported predominance of carcinoma tongue in males which is consistent with our findings.…”
Section: 11supporting
confidence: 93%
“…This indicates that environmental factors may play a vital role in the pathogenesis of HNC (Attar et al, 2010).…”
Section: Common Risk Factors For Hncmentioning
confidence: 99%